Peningkatan Pengetahuan Preeklamsia Pada Pelaksanaan Kelas Ibu Hamil Melalui Penyuluhan - Pangestuti, Restu; Ratrikaningtyas, Prima Dhewi; Sutomo, Adi Heru; Tristanti (Innovative: Journal Of Social Science Research, 2025)
Preeclampsia is a condition of pregnancy-related multisystem disorder with no definite etiology. The main cause of Preeclampsia is still uncertain. Pregnant women's knowledge about preeclampsia is still limited, which makes it a delay in recognizing pregnancy complications. Increasing the knowledge of pregnant women about preeclampsia through counseling in pregnant women classes. The research design is a descriptive correlation with a cross sectional approach. The instruments used were pretest and posttest questionnaires on knowledge about preeclampsia and the number of research subjects was 50 pregnant women. The sampling technique uses purposive sampling with the calculation of the number of samples using the Slovin formula. The results obtained using paired t-test analysis are the average difference between the pre test score and the post test score. The average score of the pretest was 59.04 and the average score of the posttest was 74.96. This shows that there is an increase in the post test score after being given counseling by 15.92. The results of the study were H0 was rejected and Ha was accepted with a p value of <0.001 (0.0000) and a confidence interval of 60.29 to 76.20 (95% CI). Knowledge of preeclampsia in pregnant women can be improved through counseling carried out during pregnant women's class activities. Counseling activities are a means that can be used by midwives when providing preeclampsia information to pregnant women.